Criminal Liability for Physical Violence in the Domestic Sphere (Analysis of Medan District Court Decision Number 1264 / Pid.Sus / 2023 / PN Mdn) - Syukur Siregar, Abdul; Sitompul, Ariman (International Asia Of Law and Money Laundering, 2024)
Many domestic violence criminal events that occur within the household, such as the decision of the Medan District Court Number 1264 / Pid.Sus.2023 / PN Mdn, where the defendant in the name of Bobby Fauzan was only sentenced to 2 (two) months in prison which was actually unworthy and appropriate for what he did to his legal wife. The research used is juridical normative, where research is done by tracing legal material through literature studies. This study is descriptive Analytical that is to analyze the data systematically. Criminal liability against perpetrators of domestic violence in Medan District Court decision number 1264 / Pid.Sus / 2023 / PN Mdn, has not reflected a fair and beneficial verdict for victims. Because between acts with normative provisions that provide mild sanctions for perpetrators are still tertullis and have not been revised. It could happen to a wife again. Whereas Article 28g paragraph (1) of the 1945 Constitution and Law No. 23 of 2004 have provided legal protection clearly and definitely. However, from the aspect of justice and benefit received by the victim for the actions of her husband does not reflect a clear Justice and benefit because the sanctions given are still mild. Thus, it is necessary for Law No. 23 of 2004 to be revised.